Isolation, Chemical Modification and In vivo Pharmacological Screening of Piperine and its Derivatives - Tasneem, Faria; Saha, Poushali; Spriha, Sabiha Enam; Rahman, Fahad Imtiaz; Sharmin, Nahid; Rahman, S M Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Piperine (1) extracted from black pepper was transformed into its derivatives piperic acid (2) and piperonal (3) with good yields (69-76%). Animal models were used to examine the compounds' in vivo peripheral as well as central analgesic and anti-inflammatory effects. In the peripheral analgesic experiment, compound 2 displayed remarkable action having writhing inhibition by 78% at 50 mg/kg dose, superior to that of 1 (74% writhing inhibition) when administered at the same dose and compared with standard diclofenac sodium (85%). Concerning central analgesic efficacy, piperonal outperformed compounds 1 and 2 at 25 mg/kg dose, with % tail-flick elongation times of 194%, 178%, and 178% at 30, 60, and 90 min, respectively. Conversely, at 50 mg/kg dose, piperic acid exhibited the highest activity, demonstrating % tail-flick elongation times of 231%, 213%, and 206% at 30, 60, and 90 min, respectively, as compared to the standard morphine (278%, 247%, and 160%) in the same duration. In anti-inflammatory property evaluation, piperonal portrayed outstanding effects with paw edema inhibitions of 57%, 66%, 76%, and 81%, respectively from 1st hour onwards, compared to standard aceclofenac (61%, 72%, 78%, and 89%) and parent compound piperine (20%, 34%, 51%, and 60%). This study suggests that piperine derivatives could act as promising leads for future drug development. Dhaka Univ. J. Pharm. Sci. 23(1): 13-22, 2024 (June)